Strategies and Tactics for Promoting Indie Game Design - Kerr, Aphra; Whitson, Jennifer R.; Harvey, Alison; Shepherd, Tamara; O’Donnell, Casey (AoIR Selected Papers of Internet Research, 2013)
This panel examines diverse ways of promoting independent or indie video game design through initiatives at the government, corporate, community, and individual levels. While the parameters of what constitutes indie game design continue to be debated (Ruffino, 2013), we will consider small teams and single authors of games who work with limited resources and use digital distribution methods. The dramatic rise in this type of game production over the past decade can be traced to a number of factors, including the initiatives each presenter will discuss during this session, along with technological shifts that have enabled broader access to online development tools, distribution channels, and microfunding opportunities via Indiegogo and Kickstarter. By increasing the diversity of video games and game production methods beyond those of major game studios, indie game design may offer a resistant alternative to mainstream games (Anthropy, 2012; Pedercini, 2012) as well as corporate production processes (Westecott, 2013). By consistently redefining what constitutes “innovation,” indie game designers and companies actively position themselves as different from the mainstream. Yet this positioning is not necessarily evenly executed, since indies often show an affinity for their large-scale counterparts (Dovey & Kennedy, 2006), even while framing themselves as resistant underdogs. Moreover, the resistance and appropriation cycle of indie game design is an important dynamic within an industry that is dominated by a few AAA game studios, where the co-optation of non-professional labour is an everyday practice and smaller companies often get acquired as they rise in prominence (Dyer-Witheford & de Peuter, 2009). As such, we describe a series of promotional strategies and tactics for bolstering indie game production as an alternative mode of production in different contexts. Michel de Certeau’s definition of strategies versus tactics – technocratic strategies “are able to produce, tabulate and impose” conformity upon spaces, “whereas tactics can only use, manipulate and divert these spaces” (1984, p. 30) – informs the variety of approaches to indie game design offered in this panel. The first paper, “Towards Creative Autonomy: Tactics for Survival,” broadly describes recent shifts in the video game industry as a backdrop for the results of surveys and action research with indies in Ireland over the past ten years. While indie game companies have grown in number over this period – spurring on attendant growth in market share and game design diversity – they have also had to contend with increased economic pressures. Second, the paper “Does Being Indie Mean Trading Financial Freedom for Creative Freedom?” discusses how the language of indie is currently being contested, appropriated, and reshaped in Montreal game development incubators. In questioning the meanings of indie, the paper explores how indie ideals are challenged within incubator walls. The third paper, “Indies, Incubators, and Inclusion: Reconfiguring Gendered Participation in Game Design,” presents the results of two ethnographic studies of women-only game design initiatives, contextualized in the local game design cultures of Toronto and Montreal. The possibilities as well as the limitations of these two initiatives are framed in relation to the gendered participation gap in video game production and game culture more broadly. The fourth paper, “Mixed Messages: Policing the Public/Private Boundaries of Cultural Production on the Nintendo DS,” examines the ambiguous character of videogame console modification chips (MOD chips) in the space of videogame piracy through an ethnographic study of Nintendo DS MOD communities. MOD chips enable users to act as indie designers by creating software and videogames that run on these consoles outside the typical rules and regulations of the videogame industry; the paper illuminates this understudied space of cultural production. Together, these four papers illustrate how recent initiatives to promote indie game design from both strategic and tactical perspectives are crucial within the larger terrain of video game production that shapes diversity of digital culture at the levels of both representation and labour. References Anthropy, A. (2012). Rise of the Videogame Zinesters: How Freaks, Normals, Amateurs, Artists, Dreamers, Drop-outs, Queers, Housewives, and People Like You are Taking Back an Art Form. New York, NY: Seven Stories Press. de Certeau, M. (1984). “Making do”: Uses and tactics. In S Marshall (Trans.), The Practice of Everyday Life (pp. 29-42). Berkeley: University of California Press. Dovey, J. & Kennedy, H. (2006). Game Cultures: Computer Games as New Media. Maidenhead and Milton Keynes: Open University Press Dyer-Witheford, N., & de Peuter, G. (2009).Games of Empire: Global Capitalism and Video Games. Minneapolis: University of Minnesota Press. Pedercini, P. (2012). Toward independence – Indiecade 2012. Retrieved from http://www.molleindustria.org/blog/toward-independence-indiecade-2012-microtalk/. Ruffino, P. (2013). Narratives of independent production in video game culture. Loading… The Journal of the Canadian Game Studies Association 7(11). Retrieved from http://journals.sfu.ca/loading/index.php/loading/article/view/120/155. Westecott, E. (2013). Independent game development as craft. Loading… The Journal of the Canadian Game Studies Association 7(11). Retrieved from http://journals.sfu.ca/loading/index.php/loading/article/view/124/153.